Use of Technology and Its Association With Academic Performance and Life Satisfaction Among Children and Adolescents - Ramírez, Saray; Gana, Sofía; Garcés, Soledad; Zúñiga, Teresa; Araya, Ricardo; Gaete, Jorge (Frontiers in Psychiatry, 2021)
Introduction: In the last years, there has been a rise in the use of technology among children and adolescents, which has led to a greater concern about its impact on their socioemotional and cognitive development. Aims: To explore the time spent using technology, the risk perception of its use by students, and the association between frequency of technology use and life satisfaction and academic performance among children and adolescents in Chile. Additionally, we explored the mediating effect of sleep deprivation on these outcomes. Methods: This is a cross-sectional study, where 2,440 students (9-12 years old) from 13 schools participated. Data was collected using an online survey answered by students during school hours. The association analyses were performed using multivariable regression models considering life satisfaction and academic performance as dependent variables. Additionally, mediating analyses were conducted using structural equation modeling. Results: Time watching television and using cellphones were similar on weekdays, and playing video games was the most frequent activity during weekends. A 42.1% of students reported playing online video games with strangers, and 12.7% had sleep deprivation. Lower self-reported academic performance was associated with cyberbullying victimization, sleep deprivation, being hacked, exposure to violent content, time spent using cell phones during weekdays and weekends, and playing video games during weekdays. Students who perceived that playing video games after 9 pm affected their sleep had a higher academic performance. There was a clear mediating effect of sleep deprivation in the relationship between time spent using a cellphone during weekdays and weekends and playing video games during weekdays and GPA. Conclusions: Time spent using technological devices was not associated with life satisfaction; however, the time spent using cell phones and playing video games was related to lower self-reported academic performance, mediated by sleep deprivation. Future research may focus on a better understanding of the mechanisms involved in the effect of technology use on sleep routines among adolescents and potential interventions to reduce its impact on academic performance.